Impact of brand concept and AI agent gender on brand experiences in virtual spaces - Joo-Eon Jeon (Global Business & Finance Review (GBFR), 2024)
Purpose: This study investigates the anticipated differences between consumers' interactions with AI agents and brand experiences in virtual brand spaces, based on brand concepts and the agent's gender. Design/methodology/approach: To test the proposed hypotheses, a 2 (Brand Concept: Functional Brand vs. Experiential Brand) 2 (AI agent's gender: male vs. female) experimental design was used. Findings: Consumers may expect continuous dialogue, and entertainment or search experiences, while receiving guidance on functional brand Concepts from a male AI agent, because of higher confidence and trust. However, when guided by a female AI agent on experiential brand concepts, continuous dialogue could be anticipated because of greater sensory and emotional experiences. Research limitations/implications: The analysis yields two key academic implications. First, the role of brand concept in achieving a continuous grounding between consumers and AI agents was identified. Second, the role of the AI agent's gender in enhancing brand experience in virtual spaces was identified. Originality/value: This study investigates how consumers encountering AI agents in virtual brand spaces evaluate grounding and brand experiences differently based on the agent's gender. It was anticipated that grounding with AI agents would vary according to the brand concept emphasized in virtual spaces, and that the intensity of brand experience in interaction with the AI agent would also differ.
Keywords: 650; AI Agent; Gender; Brand Concept; Grounding; Experience